Functional mixed-effect models for electrophysiological responses - Davidson, D.J. (Нейрофизиология, 2009)
In electro/psychophysiological experiments, linear mixed-effect modeling is an effective statistical technique for data repeatedly observed from the same experimental participants or stimulus items. This review describes the application of mixed-ef fect modeling to functional responses, in particular those observed in event-related EEG or MEG experiments, using a discrete wavelet transform. The technique is illustrated with a design with several covariates, and procedures for generating posterior samples and computing a Bayesian false discovery rate are described. Лінійне моделювання з урахуванням змішаних ефектів (mixed-effect modeling, MEM) є корисною статистичною методикою при інтерпретації даних, які повторно реєструються в умовах тестування одного й того самого учасника дослідження або використання ідентичного порядку стимулів у електро-/психофізіологічних експериментах. В огляді описано використання МЕМ при аналізі функціональних відповідей (зокрема, пов’язаних з подією феноменів, що спостерігалися в електро- або магнітоенцефалографічних дослідженнях) із застосуванням дискретного вейвлет-перетворення.